2022
DOI: 10.1186/s12915-022-01322-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer-promoter interaction maps provide insights into skeletal muscle-related traits in pig genome

Abstract: Background Gene expression programs are intimately linked to the interplay of active cis regulatory elements mediated by chromatin contacts and associated RNAs. Genome-wide association studies (GWAS) have identified many variants in these regulatory elements that can contribute to phenotypic diversity. However, the functional interpretation of these variants remains nontrivial due to the lack of chromatin contact information or limited contact resolution. Furthermore, the distribution and role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Another group of methods is designed to search for all possible DNA and RNA contacts in a cell (MARGI [12], GRID-seq [13, 14, 15], ChAR-seq [16], iMARGI [17, 18], RADICL-seq [19], Red-C [20]). We will call this group of methods “all RNAs to all DNA loci”, or “all-to-all”.…”
Section: Introductionmentioning
confidence: 99%
“…Another group of methods is designed to search for all possible DNA and RNA contacts in a cell (MARGI [12], GRID-seq [13, 14, 15], ChAR-seq [16], iMARGI [17, 18], RADICL-seq [19], Red-C [20]). We will call this group of methods “all RNAs to all DNA loci”, or “all-to-all”.…”
Section: Introductionmentioning
confidence: 99%
“…In humans and other animals, a large number of cis-regulatory elements have been determined using the ChIP-seq technique. Many cis-regulatory elements significantly contribute to phenotypic variation in complex traits [48,83,84]. We then examined the elements that may regulate the differential expression of the ADRA2A and some immune response genes identified in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has identified the genomic localization of H3K4me3 and H3K27ac in pig placentas by chromatin immunoprecipitation sequencing (ChIP-seq) [43]. Recently, many studies investigated the architecture of chromatin in multiple tissues from different pig breeds and characterized the function of the cis-regulatory elements marked by H3K4me3 and H3K27ac in the pig genome [44][45][46][47][48]. A recent study revealed that the myometrium undergoes a cascade of epigenetic events during active labor and postpartum in the mouse model, indicating that histone modifications contribute to regulating gene expression in the myometrium [49].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, integrative analyses of GWAS and epigenomics provide important insights and resources for understanding both methylation and histone epigenetic regulation, as well as their interaction and roles in complex trait genetics (Li et al, 2022). Integration of GWAS with others omics data, including metabolomics (Wang & Kadarmideen, 2020), proteomics and the microbiome (Power et al, 2017), has been applied to identify relevant SNPs of potential importance.…”
Section: Den T I F Icat Ion Of Gen Et Ic Loc I a S Soc I At Ed W I T ...mentioning
confidence: 99%
“…However, a large proportion of those genetic loci do not affect protein‐coding regions directly, and remain mostly intergenic or unannotated, which hinders the further interpretation of the molecular basis of muscle development. To bridge this gap between genetic variation and muscle phenotype, many studies have been designed to profile a diversity of molecular processes affected by non‐coding variants (Li et al, 2022), which reveals thousands of genetic variants impacting gene expression, mRNA splicing, DNA methylation, histone acetylation, RNA editing and protein levels (Figure 2). Joint analysis of expression QTL (eQTL) with phenotypic QTL (pQTL) segregation in pig longissimus dorsi muscle revealed many candidate genes significantly associated with pQTL for growth traits (Cheng et al, 2019; Velez‐Irizarry et al, 2019).…”
Section: Identification Of Genetic Loci Associated With Muscle Traitsmentioning
confidence: 99%